Debt Sustainability under Catastrophic Risk : The Case for Government Budget Insurance - Cavallo, Eduardo (IMF Working Papers; Working Paper, 2008)
Natural disasters are an important source of vulnerability in the Caribbean region. Despite being one of the more disaster-prone areas of the world, it has one of the lowest levels of insurance coverage. This paper examines the vulnerability of Belize's public finance to the occurrence of hurricanes and the potential impact of insurance instruments in reducing that vulnerability. The paper finds that catastrophic risk insurance significantly improves Belize's debt sustainability. In addition, the methodology employed makes it possible to estimate the appropriate level of insurance, which for the case of Belize is a maximum coverage of USD 120 million per year.